Post-flood waste characterization test in the Municipality of Athiémé - Vifan Eric, Sebo (European Scientific Journal, ESJ, 2022)
In the municipality of Athiémé, recurrent and cyclical flood are serious generators of waste. These waste referred as post-flood waste, as it is not the subject of any information or study, are not consider neither the authorities responsible for the management of household waste nor the crisis management unit flooding in the municipality of Athiémé. This study was initiated to induce awareness among the various actors whose this responsibility fall. To make success the study, the methodological approach used proposes a characterization of post-flood waste. This characterization is done in two stages consisting of a typological characterization and a mass estimation of post-flood waste. The typological characterization relied mainly on the material goods and dwellings of the inhabitants, located in the geographical influence of the flood. As for the mass estimation of post-flood waste, it has been possible by multiplying the number of issues exposed to flood risk by the quantity of waste produced per unit of stakes, the issues here being the material goods and the buildings of inhabitants. The application of this methodological approach shows that in the Commune of Athiémé, post-flood waste consists mainly of waste resulting from the partial or total destruction of dwellings (48%), furniture waste (33%) and mixed waste (19%). All of this waste, according to the magnitude of the floods, gives an average mass which varies from 714,846 kg (ie 714,846 tons) with the big flood of 2010 to 139,672 kg (or 139,672 tons) in 2016. This colossal mass post-flood waste, although reused at 38% for waste resulting from the destruction of the building, must be taken into account by the authorities at various levels in terms of their management. In this perspective, suggestions were made for their upstream estimation, with well-defined parameters, data and tools.